2018
DOI: 10.31235/osf.io/2bkzx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indigenous residential segregation in towns and cities, 1976–2016

Abstract: Indigenous people tend to live in different parts of Australian towns and cities than the non-Indigenous population. This is due to a combination of historic and contemporary government policies, the agency of Indigenous people, and the constraints placed on residential location by the interaction of the housing and labour markets. This study traces the trajectory of Indigenous residential segregation in 60 Australian towns and cities, using census data from 1976 to 2016. Segregation is measured using the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Those living on Aboriginal land in the Northern Territory are not only the most impoverished people in Australia, but also they are becoming relatively poorer. 48 This trend is the result of policy to discourage and even financially penalise those who live on their country. The most recent estimates from a Centre for Appropriate Technology (2016) survey indicated that there are over 600 homelands in the Northern Territory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those living on Aboriginal land in the Northern Territory are not only the most impoverished people in Australia, but also they are becoming relatively poorer. 48 This trend is the result of policy to discourage and even financially penalise those who live on their country. The most recent estimates from a Centre for Appropriate Technology (2016) survey indicated that there are over 600 homelands in the Northern Territory.…”
Section: Resultsmentioning
confidence: 99%
“…The ALRA remains the most progressive and comprehensive land rights law in Australia. It has delivered a form of inalienable collective title over an estimated [48][49][50] per cent of the Northern Territory (635,000-650,000 sq kms) -with exact acreage remaining difficult to calculate because some claims are still being legally resolved. Ownership of land has afforded many 1 I would like to thank Sana Nakata, Melinda Hinkson, Shino Konishi, Michael Dillon, Karrina Nolan and the editors of this book for critical engagement with an earlier version of this chapter.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Segregation of Indigenous people onto reservations, missions and reserves 39 effectively reduced their ability to participate in the cash economy or to own homes, while both implicit and explicit policies segregated Indigenous people in urban neighbourhoods and in educational settings. 40–42 Because many academic institutions privilege enrolment of the children of alumni, the legacy of exclusionary policies can endure and continue to perpetuate harms well beyond the overt end of these policies. When scientists are predominantly academics, they will therefore tend to be White elites.…”
Section: An Unnatural Gapmentioning
confidence: 99%